The Influence of Organizational Support Employee Engagement and Work Ethic on Employee Performance in The Oil and Gas Company Eni Indonesia - Jakarta - Intan Zahralia Suprapto; Dudung Hadiwijaya; Ismail Marzuki (Eduvest - Journal of Universal Studies, 2025)
The aim of this research is to analyze the influence of organizational support, employee engagement and work ethic on employee performance in oil and gas companies, ENI Indonesia - Jakarta. This research uses a quantitative approach with data collection techniques in the form of questionnaires and literature studies. The population and sample used were ENI Indonesia employees, totaling 90 respondents. The research results show that Work Ethic does not have a significant effect on Employee Performance even though it has a positive value. Organizational support has a positive and significant effect on employee performance. Employee Engagement has a positive and significant effect on Employee Performance. Meanwhile, organizational support, employee engagement and work ethic simultaneously have a positive and significant effect on employee performance.